Using Canvas LMS learning outcomes assessment and program improvement - Frederick Burrack (Academic Chairpersons Conference Proceedings, 2022)
This session will provide a step-by-step process of creating program outcomes in Canvas. These outcomes are aligned with assessment tasks through the scoring devices used in courses, internships, or other course-based means through which students demonstrate outcomes proficiencies. The session will provide a foundational understanding of the architecture of the Canvas Assessment Portal and how it connects with assessment tasks to automate data collection. Processes of working with programs and faculty will be shared that have been found to enable ownership of assessment processes. The session will end with the process of preparing data for analysis by faculty and program directors. Examples of analysis tables and graphs using PowerBI will be used to encourage questions and discussion.
Keywords: Assessment; Learning; Effectiveness; Improvement